Estimula????o cognitiva em idosos sedent??rios com transtorno cognitivo leve - Farias, Alyne Matos Napole??o (2018)
In Brazil the number of elderly people is increasing and this transformation in the age structure is taking place without an improvement of the living conditions. With increased life expectancy there is a greater probability of chronic and degenerative diseases, such as Mild Cognitive Disorder (MCD). The use of cognitive stimuli through cognitive stimulation therapies (CST) causes them to regress and / or interfere with advancement. The objective was to analyze changes in cognitive profile, with emphasis on memory, before and after the execution of cognitive stimulation workshops, as well as to identify socioeconomic characteristics of sedentary elderly people who attend the Mixed Health Unit of Taguatinga, Federal District (UMS-DF). It was a descriptive experimental quantitative study, with elderly (???60 years), diagnosed with MCD. The composite sample of 9 elderly of the OEC in the experimental group (G1) and 10 elderly did not undergo intervention in the control group (G2). The data collection was done by structured interview, application in the first and last meeting of the mini mental state examination, verbal fluency, clock, memory of figures and list of words. The CST offered to the G1, stimulation techniques were used, for one hour, weekly, in 10 meetings. In G2, daily life activities were reported for the same period, without cognitive stimulation. The descriptive data were evaluated by means of descriptive measures: means, standard deviations, median, absolute and relative frequency, with p <= 0,05. The chi-square test and t-test were applied using the SPSS 20.0 program and the R. software. Results showed mean age of 75 ?? years, 84.2% female, 89.5% retired and 89.5% widowed. 17 elderly (89.5%) reported better memory a year ago. After CST, 8 (88.9%) elderly of the G1 considered their current memory as good. Although the G1 elderly had higher scores in all tests after the CST, the difference between the tests was not significant (p = 1.0). No significant differences were found in the Miniexame of the Mental State (p = 0.436). The test of the clock design evidenced the low level of schooling. G1 (p> 1) and G2 (p = 0.621), the tests were not statistically significant, affirming no or almost no change in the cognitive profile. In the tests of verbal fluency (p = 0.367), word memory and figures (p = 0.351), G2 showed no recovery in recall, despite reporting an increase in group sociability. It was concluded that although the CST do not have significant results, they have a visible effect on social integration, exchange of experiences and personal empowerment. This method can help nursing to design more effective methods and implementations for the treatment and rehabilitation of not only elderly people with MCD, but with different cognitive conditions. Perhaps longer-term studies can improve such outcomes and encompass the positive aspects of physical activity in the cognitive area.